High Q realization of quasi dual-mode dual band bandpass filter - Sovuthy, C. (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper introduces a new design of dual-band bandpass filter based on coaxial line. The two passbands are achieved by connecting two stepped-impedance quasi-dual-mode resonators in parallel. Experimental prototype is fabricated and presented. The measured result shows that the coaxial filter has two passbands at 773 MHz and 880 MHz with the bandwidth of 1 and 0.4 respectively. In addition, each band of the filter has two resonances by using only one coaxial resonator structure with the electrical length of 120Â° to achieve miniaturization. Â© 2017 IEEE.